Sosialisasi Pendidikan Anti Korupsi Sebagai Upaya Pencegahan Perilaku Korupsi Pada Siswa Kelas 5 Di SDN 8 Teluk Pandan Kabupaten Pesawaran - Arizal Eka Putra; Arinie Izzataqie Latifa; Ika Ardiyanti; Indriani Lestari; Tomi Andriko; Cahya Permata Sari (Universitas Kristen Indonesia Toraja, 2023)
Corruption can be defined as bad habitual behavior and is a common phenomenon in society. This concern arises because the perpetrators of corruption exist in both government and private organizations and may also involve leaders of organizations who are role models for the younger generation. One of the efforts to reduce the increase in corruption cases is to focus on the legal aspect. However, there have not been many preventive efforts through education that have the potential to eradicate the